Holocene forest history of the eastern plateaux in the Segura Mountains (Murcia, southeastern Spain) - Carrion, J; Yll, E; Willis, K; Sanchez, P (2004)
This paper presents a mid- to late-Holocene vegetation sequence of a Juniperus thurifera-dominated area in the eastern, continental plateaux of the Segura Mountains of southeastern Spain. A mid-Holocene maximum of mesic tress is recorded in the pollen diagram between c. 6640 and 4790 cal years BP with the vegetation dominated by deciduous oaks. A dramatic decline in deciduous oaks occurred from approximately 4700 cal years BP to be replaced initially by evergreen oak, and then junipers and other xerophytes from c. 4500 cal years BP. This trend of xericness in the vegetation is coherent with regional and extra-regional palaeoclimatic records for increased mid-Holocene aridity. Significant anthropogenic modification of the vegetation occurred in this region from c. 1350 cal years BP represented by a large reduction in all tree taxa (except Juniperus) and increases of thorny scrub and nitrophilous assemblages. Increased fire incidence, pastoralism, and arboriculture were associated with this anthropogenic activity. We conclude that present-day J. thurifera-dominated communities in this region have become established through a combination of two predominant processes; increased aridification from c.4500 cal years BP and anthropogenic activity from c. 1200 cal years BP. © 2004 Elsevier B.V. All rights reserved.